2023
DOI: 10.1002/slct.202204270
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Temperature‐/pH‐Responsive Hydrogels for Drug Delivery

Abstract: A temperature-/pH-responsive hydrogel was successfully prepared by in situ free radical polymerization of N-isopropyl acrylamide (NIPAm), itaconic acid (IA), and poly (ethylene glycol) methyl ether acrylate (OEGA). The pore size, mechanical strength, and swelling ratio of the P(NIPAm-IA-OEGA) were strongly affected by the contents of IA. 5-Fluorouracil (5-Fu) was chosen as a model drug, and the maximum drug loading was 68 mg/g. P(NIPAm-IA-OEGA) had a much greater release rate in a simulated intestinal fluid en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Resin based spherical activated carbon (RSAC) was prepared according to the previous study. [22] The Co 3 O 4 À CeO 2 supported on RSAC with different Co/Ce ratios was prepared by incipient wetness impregnation (IWI) method. The RSAC was dried at 50 °C for 2 h in an oven before impregnation.…”
Section: Catalyst Ppreparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Resin based spherical activated carbon (RSAC) was prepared according to the previous study. [22] The Co 3 O 4 À CeO 2 supported on RSAC with different Co/Ce ratios was prepared by incipient wetness impregnation (IWI) method. The RSAC was dried at 50 °C for 2 h in an oven before impregnation.…”
Section: Catalyst Ppreparationmentioning
confidence: 99%
“…Resin based spherical activated carbon (RSAC) was used as support, which prepared from on exchange resin through steam activation method. [22] RSAC could facilitate high dispersion of Co 3 O 4 and CeO 2 due to the high specific surface area and abundant porosity. The high specific surface area and microporous structure on the catalyst is in favor of uniform dispersion and gas adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting CGG/ACNF filament has unique core-shell structure and was comprehensively characterized and compared with silk and PGLA sutures (glycolide 90% and l-lactide 10%) for its application performance as a surgical suture, both in vitro and in vivo. Additionally, gels and multifunctional implantable microelectronic fibers 224,226,325 are widely used in drug delivery, 28,[326][327][328][329] wound healing, 93,116,330,331 tissue engineering, [332][333][334] drugeluting medical textiles, 97 cell encapsulation 335 due to their facile methods of fabrication, potential injectability, and biomedical application. [336][337][338][339][340] Because of their improved permeability, enormous surface area, and targeting ability, both nanoparticles (Ô = 1−500 nm) and microparticles (Ô = 0.1-100 µm) have found widespread use in applications involving drug delivery.…”
Section: Drug Delivery Wound Healing Tissue Engineering and Other Bio...mentioning
confidence: 99%
“…The author showed that the drug retained to a higher extent in the hydrogel under acidic conditions prevailed in gastric juice while it could be released in simulated intestinal fluid environment which makes the hydrogel a good candidate for oral drug delivery. [ 16 ] But also even more complex charged molecules like DNA or proteins can be caught and released with ionic hydrogels by electrostatic interactions which offer various biomedical applications, e.g. tissue engineering or protein therapeutics.…”
Section: Introductionmentioning
confidence: 99%